Produk Furnitur dari Metal sebagai Pengembangan Teaching Factory Politeknik Bosowa - Ulia Ridhani; Alang Sunding; Imron Burhan (Universitas Negeri Makassar, 2019)
Furniture industry is a creative industry activity that is included in craft clusters which produce productsthat can be utilized by the community, government agencies and industry.Every home,officeand industry requiresfurniture ranging from simple to luxurious furniture. Thus, people who couldlookthis opportunityhavea chance todevelop,especially if they are able to meet the customer needs.Metal furniture is furniture made from the main metalmaterial which is hollow iron, L profile, plate strip which can be combined with other materials such as wood,rubber, multiplex, and plastic which are then of high artistic value.Metal furniture is still very possible to bedeveloped because there is no business that focuses on making this product in Makassar.Therefore, this business isexpected tobea pioneer in thedevelopment of teaching factory based on construction and welding of BosowaPolytechnic.One of the furniture products is a cafe set table that is commonly used in cafes that can produceaproductthathasvaluesell.As forthe total production cost is Rp.804,300, -with the desired profit margin of 25% ofproduction costs.The production system used is “make to stock”in whichcustomers are freeto design their owndesired products.